Advanced green bioprocess of soil carbohydrate extraction from long-term conversion of forest soil to paddy field. Issue 5 (October 2021) - Toan, Nguyen-Sy; Tan, Xuefei; Phuong, Nguyen Thi Dong; Aron, Nurul Syahirah Mat; Chew, Kit Wayne; Khoo, Kuan Shiong; Thu, Tran Thi Ngoc; Thi Lim, Duong; Dong, Pham Duy; Ang, Wei Lun; Show, Pau Loke
Abstract: The present research aims to study the long-term impacts of soil extractable carbohydrate content from the conversion of forest to paddy field, using three environmentally friendly methods: ultrasound assist (37 Hz/30 min), hot water (80 °C/4 h), and cold water (25 °C/30 min). Soil samples collected at the depth of 0–15 cm from natural forest, rice paddy, and border area were extracted by distilled water at the ratio 1:10 (soil: water). Contents of soil organic carbon (SOC) and extracted carbohydrate (ECH) in the natural forest and rice paddy were similar, and higher than in border area by 50%. Results showed the highest content of ECH was extracted using hot water (304–691 mg.Carbohydrate/kg soil, 4% of SOC), followed by ultrasound (102–305 mg.Carbohydrate/kg soil, 1.7% of SOC), and the lowest amount addressed to cold-water extraction (65–252 mg.Carbohydrate/kg soil, 1.2% of SOC). The ECH/SOC ratios in three soil types were the same and ranged from 0.9% to 4.2%. We conclude the long-term conversion of forest to rice paddy maintain both SOC and ECH, furthermore, hot water extraction at 80 °C/4 h is the optimum method for extraction of carbohydrate using non-chemical solvents. Graphical Abstract: ga1 Highlights: Effects of soil carbohydrate content in long-term rice paddy cultivation. First study to compare three sustainable methods of soil carbohydrate extraction. Long-term rice paddy cultivation does not affect carbohydrate content in the soil. Hot water extraction method of 80 °C/4 h showed the highest soil carbohydrate.